Ethical challenges in designing and conducting medicine quality surveys - Tabernero, Patricia; Parker, Michael; Ravinetto, Raffaella; Phanouvong, Souly; Yeung, Shunmay; Kitutu, Freddy E.; Yeong Chea, Phaik; Mayxay, Mayfong; Guerin, Philippe J.; Newton, Paul N. (Tropical medicine & international health, 2016)
In this paper we discuss the main ethical challenges related to the conduct of medicine quality surveys and make suggestions on how to address them. method Most evidence-based information regarding medicine quality derives from surveys. However, existing research ethical guidelines do not provide specific guidance for medicine quality surveys. Hence, those conducting surveys are often left wondering how to judge what counts as best practice. A list of the main ethical challenges in the design and conduct of surveys is presented. results and conclusions It is vital that the design and conduct of medicine quality surveys uphold moral and ethical obligations and analyse the ethical implications and consequences of such work. These aspects include the impact on the local availability of and access to medicines; the confidentiality and privacy of the surveyors and the surveyed; questions as to whether outlet staff personnel should be told they are part of a survey; the need of ethical and regulatory approvals; and how the findings should be disseminated. Medicine quality surveys should ideally be conducted in partnership with the relevant national Medicine Regulatory Authorities. An international, but contextually sensitive, model of good ethical practice for such surveys is needed.
Keywords: Ethics; Poor quality; Medicines; Surveys; Falsified and substandard medicines; Counterfeit